Availability of comparative real-world evidence research in Medicare patients: implications for Centers for Medicare and Medicaid Services drug price negotiations - Ashley Jaksa; Patrick J Arena; Nicolle Gatto (Becaris Publishing Limited, 2023)
Aim: To evaluate the availability of published comparative real-world evidence (RWE) studies in Medicare patients for the ten drugs set to undergo Centers for Medicare and Medicaid Services (CMS) price negotiations in 2026. Materials & methods: A scoping review was completed in MEDLINE/PubMed to evaluate the availability of comparative RWE investigations conducted among Medicare-eligible patient populations in the US for the following drugs: apixaban, rivaroxaban, sitagliptin, ibrutinib, empagliflozin, etanercept, dapagliflozin, sacubitril/valsartan, ustekinumab and insulin aspart. Results: Of the 170 realworld comparative studies identified, 55 (32.4%) used Medicare real-world data (RWD) while 34 (20.0%) used commercial claims data in conjunction with either Medicare Advantage or Medicare Supplementary databases. The number of studies varied considerably by drug with apixaban and rivaroxaban studies accounting for the majority (i.e., 67.1%) of comparative RWE studies. Approximately a third or less of the comparative RWE studies were conducted in CMS RWD per drug. Conclusion: Our results demonstrate there is a considerable amount of comparative RWE for apixaban, rivaroxaban, and etanercept but limited comparative RWE for the other drugs set to undergo CMS price negotiations in 2026; additionally, our findings set up a number of next steps (e.g., risk of bias assessments) for further exploration of the available evidence base. Overall, CMS and manufacturers should consider proactively generating highquality comparative RWE studies in the Medicare population to ensure that future price negotiations are based on robust evidence.